UNVEILING THE DIGITAL LANDSCAPE: SCHOOL SOCIAL WORKERS’ KNOWLEDGE AND PERCEPTIONS OF ADOLESCENT SEXTING IN GAUTENG SCHOOLS, SOUTH AFRICA - Adlem, Anri (Social Work/Maatskaplike Werk, 2025)
In today’s digitally interconnected world, adolescent sexting is a critical concern for school social workers. The study aimed to explore the knowledge and perceptions of school social workers regarding adolescent sexting in Gauteng and their actions in response to it. A qualitative approach was adopted utilising a phenomenological research design supported with elements of explorative, descriptive and contextual elements to highlight the multifaceted nature of sexting, which is influenced by societal dynamics, emotional needs and evolving family structures. Non-probability sampling techniques, including purposive and snowball sampling, were utilised to select 36 participants, representing diverse perspectives in the school social work profession. Data collection involved face-to-face and virtual semi-structured interviews, guided by a structured interview guide. Data analysis followed the methodological framework outlined by Tesch in Creswell, encompassing eight steps to systematically analyse interview transcripts. Sexting behaviours were examined through the lens of ecological systems and social learning theories, with an emphasis on the need for comprehensive interventions. Recommendations include targeted training programmes, collaboration with experts, integration into school policies, educational seminars for parents and continuous professional development for social workers. This research provides nuanced insights to support evidence-based interventions as well as to safeguard adolescent wellbeing in the digital age.